Measurement of levels of drinking - O' Connor, JF (Economic & Social Studies, 1973)
A study that deals with the drinking behaviour of a particular group, must cope with the problem of obtaining accurate measures of the alcohol consumed by the respondents. This paper is concerned with the literature and research findings relevant to the measurement of levels of drinking. It is divided into two sections. The first deals with the use of measures in general studies on drinking behaviour, and the second section concerns itself with the study of the young problem drinker and the methodology employed in studies of this nature.
Keywords: Alcohol; Consumption; Ireland